Surface Tension Profiles under Various Microwave Radiation Modes - Asakuma, Y.; Kanazawa, Y.; Parmar, Harisinh Bhikhubhai; Pareek, Vishnu; Phan, Chi; Evans, G. (David Publishing, 2014)
Surface tension of fluids is crucial for multiphase systems and is often controlled during industrial processes by introducing surfactants. In this study, effect of various microwave radiation modes on surface tension of water was investigated as an alternative physical method to manipulate the surface tension without using chemicals. It is found that surface tension decreased quickly whiletemperature increased during microwave. Once the radiation was turned off, the temperature returned rapidly as expected. However, surface tension did not recover so much. The minimum surface tension after microwave radiation depended on the power. Moreover, a second radiation can have additional reduction on surface tension.